Constructing Ottoman identity: Namik Kemal's intellectual legacy - Bektas, Erhan (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2025)
Nam & imath;k Kemal advocated for a constitutional government to unite the diverse populations of the Ottoman Empire under a shared identity. He believed that such a system would strengthen people's sense of belonging, prevent separatist tendencies, and foster social unity. This study examines Kemal's contributions to debates on the constitutional monarchy in the Ottoman Empire and his support for it. His vision highlighted consultation and participatory governance as essential tools for enhancing social cohesion among Ottoman subjects.
Keywords: H & uuml; rriyet newspaper; Nam & imath; k Kemal; young Ottomans; constitutional monarchy; Ottoman identity; Government & Law